Time matters less when outcomes differ: uni-modal versus cross-modal comparisons in intertemporal choice - Cubitt, Robin P.; McDonald, Rebecca; Read, Daniel (INFORMS (Institute for Operations Research and Management Sciences), 2018)
Uni-modal intertemporal decisions involve comparing options of the same type (e.g. apples now versus apples later), and cross-modal decisions involve comparing options of different types (e.g. a car now versus a vacation later). As we explain, existing models of intertemporal choice do not allow time preference to depend on whether the comparisons to be made are uni-modal or cross-modal. We test this restriction in an experiment using the delayed-compensation method, a new extension of the standard method of eliciting intertemporal preferences that allows for assessment of time preference for non-monetary and discrete outcomes, as well as for both cross-modal and uni-modal comparisons. Participants were much more averse to delay for uni-modal than cross-modal decisions. We provide two potential explanations for this effect: one drawing on multi-attribute choice, the other drawing on construal level theory.